To the Problem of Automation of Accounting and Analytical Process in the System of Information and Economic Security of the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2015)
Current trends of automation of accounting and analytical process of accounting entities in Ukraine are determined in the article. Main software used for automate accounting processes including: «1C», «Best Zvit Plus», «Parus» were compared. Stages necessary for achievement of information security by means of effective use of the automated accounting systems were allocated. Attention was focused on a problem of automated accounting systems functioning in terms of economic security tools and prevention of unauthorized information use on the enterprises
Keywords: accounting and analytical software products, automation of accounting and analytical processes, efficiency of activities of the entity, managerial «1C» software complex, the security of information